High-resolution scanning electron microscopy of dopants in p-i-n junctions with quantum wells - Barkay, Z; Grunbaum, E; Shapira, Y; Wilshaw, P; Barnham, K; Bushnell, B; Ekins-Daukes, N; Mazzer, M (2004)
We have studied the electric field distribution in p-i-n structures with multi-quantum wells (MQW) using the method of dopant (ionization potential) contrast in high resolution (with a cold field emission electron gun) scanning electron microscopy (HRSEM). The samples are GaAs-based ternary compound layer structures used for high-efficiency solar cells, consisting of p-i-n junctions, in which various numbers of InGaAs quantum wells have been inserted into the intrinsic (undoped) region. The results show an increasing secondary electron signal across the n, i and p regions while the series of 8 nm wide quantum wells and their corresponding barriers within the i-region are clearly distinguished. The field distribution is obtained by differentiating the dopant contrast curves. This study highlights the capability of HRSEM to provide information on active doping and associated electric fields within electronic nanostructures.